George Brettingham Sowerby, I, II & III: their conchological publications and Molluscan taxa - Petit, Richard E. (Zootaxa, 2009)
Several members of the Sowerby family were artists and authors of natural history works in the 19 th Century. Three of them, George Brettingham Sowerby, his son, and his grandson (I, II & III respectively) are especially known for their molluscan publications. The first to bear the name is best known for his Genera of recent and fossil shells and for initiating the Thesaurus Conchyliorum, the latter work being finished by his son and grandson. He was also primarilyresponsible for the Conchological Illustrations for which his son produced the plates and several monographs. In addition to the Illustrations and much of the Thesaurus, G. B. Sowerby II is known for his Manual of Conchology and for the final volumes of Reeve’s Conchologia Iconica. The third generation of this line finished the Thesaurus and published an enlarged edition of his father’s Illustrated Index of British Shells. He published numerous papers in journals and is best known for a series of papers on mollusks of South Africa. Complete molluscan bibliographies for all three G. B. Sowerbys are compiled and collated and a list of their molluscan taxa is here given for the first time.